2012
DOI: 10.5740/jaoacint.cs2012_01
|View full text |Cite
|
Sign up to set email alerts
|

Gliadin as a Measure of Gluten in Foods Containing Wheat, Rye, and Barley—Enzyme Immunoassay Method Based on a Specific Monoclonal Antibody to the Potentially Celiac Toxic Amino Acid Prolamin Sequences: Collaborative Study

Abstract: The Working Group on Prolamin Analysis and Toxicity (WGPAT) organized a collaborative study to confirm whether the two R5 antibody-based ELISA test kits are able to detect gliadin in the lower mg/kg (ppm) level. Twenty laboratories investigated 12 blind-coded samples, spiked and naturally contaminated, to show the possibility of determining traces of gliadin in heat-treated or nonheat-treated foods by ELISA. It was shown that very small amounts of gliadin (below 100 ppm) could be detected by ELISA with a repro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 3 publications
(3 reference statements)
1
15
0
Order By: Relevance
“…Several commercial enzyme-linked immunosorbent assay (ELISA) test kits suitable for the detection of gluten are available. At the time the gluten-free regulation was drafted, only the R5 monoclonal antibody-based and Morinaga Institutes of Biological Sciences (MIoBS) polyclonal antibody-based sandwich ELISAs (R5-sand and MIoBS-sand, respectively) had been validated by multiple laboratories at levels suitable for regulatory enforcement, extensively evaluated in research studies, and officially recognized by other governments or governmental agencies (1, 4 , 10,13,16,17,27). Since the 2013 gluten-free regulation, the G12 monoclonal antibody-based, A1-G12 monoclonal anti body-based, and Skerritt monoclonal antibody-based sandwich ELISAs (G 12-sand, A1-G 12-sand, and Skerrittsand, respectively) have been validated, extensively studied, and adapted to be suitable for detection of 20 ppm of gluten (2 , 18,19,21,22,25,28).…”
mentioning
confidence: 99%
“…Several commercial enzyme-linked immunosorbent assay (ELISA) test kits suitable for the detection of gluten are available. At the time the gluten-free regulation was drafted, only the R5 monoclonal antibody-based and Morinaga Institutes of Biological Sciences (MIoBS) polyclonal antibody-based sandwich ELISAs (R5-sand and MIoBS-sand, respectively) had been validated by multiple laboratories at levels suitable for regulatory enforcement, extensively evaluated in research studies, and officially recognized by other governments or governmental agencies (1, 4 , 10,13,16,17,27). Since the 2013 gluten-free regulation, the G12 monoclonal antibody-based, A1-G12 monoclonal anti body-based, and Skerritt monoclonal antibody-based sandwich ELISAs (G 12-sand, A1-G 12-sand, and Skerrittsand, respectively) have been validated, extensively studied, and adapted to be suitable for detection of 20 ppm of gluten (2 , 18,19,21,22,25,28).…”
mentioning
confidence: 99%
“…The limits of detection and quantification of the competitive R5 ELISA are 0.36 and 1.22 ng/ml of gliadins, respectively, being lower in liquid samples. Recently, a collaborative study has confirmed that the two R5 antibody-based ELISA test kits are able to detect gliadin at the lower level of the limit of detection with good reproducibility and repeatability (Immer and Haas-Lauterbach, 2012).…”
Section: Enzyme-linked Immunosorbent Assays (Elisas)mentioning
confidence: 99%
“…31,32 However, such quantitation may not give an accurate measure for other prolamins (secalin and hordein) and glutelins. Prolamins and glutelins differ in their proportions and molecular properties in wheat, rye and barley.…”
Section: ■ Introductionmentioning
confidence: 98%